Analisis Daya Saing Perdagangan Lada Indonesia - Zahira, Ghaitsa; Renaldi, Eddy (Universitas Galuh, 2024)
Pepper is a spice commodity that has the largest average export volume in Indonesia compared to other spice commodities. Indonesia's low domestic pepper consumption caused most of its production to be exported to the world market. The period used in this study is 2003-2022. This study aims to analyze the condition of Indonesia's pepper trade competitiveness using the Revealed Comparative Advantage (RCA) and Net Comparative Advantage (NCA) methods. The results of this study showed that Indonesian pepper has strong trade competitiveness and export competitiveness in destination countries.